Kyphectomy and Pedicular Screw Fixation with Posterior-Only Approach in Pediatric Patients with Myelomeningocele - BAYRİ, YAŞAR (KARGER, 2014)
Purpose: Defective posterior spinal arch and paraspinal musculature lead to progressive kyphosis in patients with myelomeningocele. Kyphosis decreases the patients' functional status and quality of life. To correct or prevent further deterioration, different surgical techniques have been introduced. Our aim is to present our clinical experience in kyphectomy and pedicle screw fixation with a posterior-only approach in pediatric patients with myelomeningocele and to discuss the technique with a review of the literature. Materials and Methods: Four patients with lumbar and 2 patients with thoracolumbar kyphosis (female: male ratio = 1: 5) secondary to myelomeningocele were operated between January 2009 and October 2012. The median age was 5.5 years (range = 3-10 years). The criteria of the patient selection for the procedure were progression of kyphosis angle, impaired truncal balance and cosmetic deformity. In this retrospective study, we performed chart reviews for demographic and clinical data. We measured the pre- and postoperative kyphosis angles by using the Cobb method on lateral x-rays. Results: The mean preoperative kyphosis angle was 114.3 degrees (range = 91-136 degrees). The mean operative time was 171.7 min (range = 110-220 min). The mean intraoperative blood loss was 450 cc (range = 300-700 cc). The postoperative mean kyphosis angle was 28.2 degrees (range = 13-33 degrees). Five patients had skin breakdown. After osteofusion was established, those 5 patients' instrumentations were explanted. No acute or immediate postoperative complications occurred. Other complications were pneumonia and urinary tract infection. In the long term, 2 patients died due to pneumonia and slit-ventricle syndrome, respectively. Conclusions: Kyphectomy and pedicle screw instrumentation with the posterior-only approach dramatically reduces the kyphosis angle that develops in patients with myelomeningocele. The method itself is less time-consuming and leads to less intraoperative blood loss compared to other methods used for this patient population. Skin breakdown is the most common short-term complication. (C) 2015 S. Karger AG, Basel
Keywords: Myelomeningocele; Kyphectomy; Pedicle screw fixation; Osteofusion; Outcome; LARGE THORACOLUMBAR MYELOMENINGOCELE; CONGENITAL KYPHOSIS; LUMBAR KYPHOSIS; LUQUE INSTRUMENTATION; OPERATIVE TREATMENT; KYPHOTIC DEFORMITY; SPINAL DEFORMITY; CHILDREN; MYELODYSPLASIA; MANAGEMENT